Isokinetic strength measurements in early knee osteoarthritis - (:unkn) unknown (My University, 2009)
Objectives: One of the most important reasons for locomotor dysfunction and disability in patients with knee osteoarthritis (OA) is muscle weakness in the lower extremity. The aim of this study was to compare the isokinetic knee muscle strength of patients with early knee OA with those of healthy people. Patients and Methods: Fifty-one patients with bilateral knee osteoarthritis who were radiologically graded as stage I or II and forty-three healthy subjects were enrolled. Western Ontario and McMaster Universities Osteoarthritis Index and 100 mm VAS were used to assess patients with knee OA. Manual muscle strength testing for quadriceps muscle and circumference measurements 10 cm above the midpatellar line were performed. Bilateral isokinetic (concentric/concentric) knee flexion and extension with the protocol of 60 degrees/sec (four repetitions), 180 degrees/sec (four repetitions) and 240 degrees/sec (20 repetitions) were performed. Results: Regarding manual muscle testing of knee OA group, quadriceps muscle strength in six knees were 4/5 and in 96 knees were 5/5; whereas in the control group only two knees had 4/5 and the rest 84 knees had 5/5 muscle strengths (p=0.22). Thigh circumference measurements were statistically similar in this regard (all p values > 0.05). In all velocities knee flexor and extensor isokinetic muscle strength values were found to be significantly lower in patients with knee OA compared to healthy subjects (p<0.05). Patients with stage I OA had greater muscle strength than those of stage II (p<0.05). Conclusions: Whether being a cause or a consequence of knee OA, muscle strength loss which cannot be detected during clinical examination appears to be present during isokinetic measurements.
Keywords: Isokinetic testing; Knee; Muscle strength; Osteoarthritis